URBAN HEALTH DILEMMAS AND STRATEGIES FOR IMPROVEMENT IN NIGERIA - Bamidele , Grace Olufunmilayo (Research Journal of Health, Medicine and Nursing, 2024)
Rapid urbanization in Nigeria has led to significant public health challenges, including overcrowding, limited access to healthcare, environmental pollution, and socioeconomic disparities. This article examines the multifaceted factors contributing to health challenges in urban Nigeria and explores strategies, successes, and recommendations for addressing them. Statement of the Problem Urban areas in Nigeria face complex public health challenges, including inadequate healthcare infrastructure, environmental pollution, and social inequalities, which pose significant barriers to improving health outcomes and wellbeing for urban residents. Qualitative method of study was employ in comprehensive review of existing literature, including peer-reviewed research articles, government reports, and policy documents, to analyze the public health challenges in urban Nigeria and identify successful interventions, community-driven projects, and partnerships between government and non-governmental organizations (NGOs) for health improvement. The study find out that the public health challenges in urban Nigeria are shaped by socioeconomic disparities, infrastructure inadequacies, environmental pollution, and a lack of healthcare infrastructure and resources. These challenges exacerbate health inequities and hinder efforts to improve health outcomes in urban areas. Successful public health initiatives, such as mobile health clinics, mass immunization campaigns, and community-driven health projects, have demonstrated the effectiveness of targeted interventions, community engagement, and partnerships between government and NGOs in improving health outcomes and fostering community empowerment. The study conclude by recommending addressing public health challenges in urban Nigeria include strengthening integrated health systems, empowering communities, promoting health education and awareness, fostering multi-electoral partnerships, investing in infrastructure and environmental sustainability, addressing social determinants of health, promoting research and innovation, building resilience and preparedness, and promotion equity and inclusivity.